Open heart surgery in Nigerian children the need for international and regional collaboration: The Bayelsa and Enugu experience - FA, Ujunwa; AS, Ujuanbi; JM, Chinawa; DO, Allagoa; B, Onwubere (Journal of Cardiology and Cardiovascular Medicine, 2021)
Background: Children with congenital heart diseases (CHD) often require palliative or definitive surgical heart interventions to restore cardiopulmonary function. Lack of early cardiac intervention contributes to large numbers of potentially preventable deaths and sufferings among children with such conditions. Objectives: The aim of this study was to highlight our experience and the importance of international and regional collaboration for open heart surgery in children with CHD and capacity building of local cardiac teams in Bayelsa and Enugu States. Methodology: In November 2016, a memorandum of understanding (MOU) was signed by the managements of FMC, Yenagoa, Bayelsa State, UNTH, Enugu and an Italian-based NGO- Pobic Open Heart International for collaboration in the area of free open heart surgery for children with CHDs and training of local cardiac teams from both institutions either in Nigeria or in Italy. Patients for the program were recruited from Bayelsa and Enugu States with referrals from all over the country with combined screening and selection done in UNTH. Selected patients were operated on and funded free of charge by the Italian NGO. Hands on training of the local cardiac teams and cardiac intervention was done twice yearly in Nigeria. Result: From inception of the program in November, 2016 to May, 2019 a total of 47 children (21 Males, 26 Females; age range 6 months to 14 years) with various types of congenital heart defects had free open heart surgery from the program with 41 surgeries done in UNTH & 6 in Italy (complex pathologies). Also, home cardiac teams from UNTH and FMC, Yenagoa gained from on-site capacity training & retraining from the Italian cardiac team both in Nigeria and in Italy. The Success rate was 95.7% (44) and Case Fatality rate was 4.3% (2). Conclusion: There is a great efficacy in early cardiac intervention. This is with respect to a high success rate and minimal Case Fatality seen in this study. This was achieved through Regional and international collaboration.